2018
DOI: 10.1007/s12035-018-0972-5
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Enhances Hippocampal Synaptic Plasticity and Improves Memory Performance in Huntington’s Disease

Abstract: Deficits in hippocampal synaptic plasticity result in cognitive impairment in Huntington's disease (HD). Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide that exerts neuroprotective actions, mainly through the PAC1 receptor. However, the role of PACAP in cognition is poorly understood, and no data exists in the context of Huntington's disease (HD). Here, we investigated the ability of PACAP receptor stimulation to enhance memory development in HD. First, we observed a hippocampal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 84 publications
5
48
0
Order By: Relevance
“…To evaluate possible effects of meridianins and lignarenone B in neuronal structural plasticity, primary cortical neurons were treated at 4DIV with 10 µM of these marine molecules (highest dose) since it was the dose of meridianins with the best GSK3βinhibition capacity. As we previously described for this type of in vitro approach [70,81,82], three days after the treatment we analysed morphological characteristics of the imaged neurons stained for MAP2 by using the Sholl analysis (Figure 7). The results of meridianins, indicated that the number of intersections in the treated cultures were increased compared with the non-treated condition (two-way ANOVA analysis; interaction effect, number of dendrites, F 7, 536 = 55.91, p < 0.0001) ( Figure 7A,B).…”
Section: Meridianins and Lignarenones Regulate Neurite Complexity In mentioning
confidence: 99%
“…To evaluate possible effects of meridianins and lignarenone B in neuronal structural plasticity, primary cortical neurons were treated at 4DIV with 10 µM of these marine molecules (highest dose) since it was the dose of meridianins with the best GSK3βinhibition capacity. As we previously described for this type of in vitro approach [70,81,82], three days after the treatment we analysed morphological characteristics of the imaged neurons stained for MAP2 by using the Sholl analysis (Figure 7). The results of meridianins, indicated that the number of intersections in the treated cultures were increased compared with the non-treated condition (two-way ANOVA analysis; interaction effect, number of dendrites, F 7, 536 = 55.91, p < 0.0001) ( Figure 7A,B).…”
Section: Meridianins and Lignarenones Regulate Neurite Complexity In mentioning
confidence: 99%
“…In addition, studies are gradually revealing the modulatory function of PACAP in neurodevelopment and neuroprotection, which might give further explanation for its involvement in ASD, which is one neurodevelopmental disorder. As further evidence, PACAP can stimulate the growth of both axons (Ogata et al, 2015) and dendritic spines (Cabezas-Llobet et al, 2018) under normal or disease conditions. Moreover, PACAP receptor PAC1 also mediates the differentiation and migration of cortical neuronal progenitors (Adnani et al, 2015).…”
Section: Pacapmentioning
confidence: 67%
“…Electrophysiological studies reveal that PACAP improves synaptic plasticity in mouse hippocampus (Cabezas-Llobet et al, 2018), and increases both frequency and amplitude of excitatory postsynaptic currents (EPSCs) of autonomic synapse (Starr and Margiotta, 2017), giving clues of how PACAP is involved in the autism-related behaviors. In addition, studies are gradually revealing the modulatory function of PACAP in neurodevelopment and neuroprotection, which might give further explanation for its involvement in ASD, which is one neurodevelopmental disorder.…”
Section: Pacapmentioning
confidence: 99%
“…These observations indicated that PACAP-27/38 enhanced neuroprotection against acute ischemic stroke via increased expression of neurotrophic factors [28]. Additionally, delivering PACAP38 intranasally in Huntington's disease mouse models mitigated disease-related deficits by restoring cognitive function and PAC1R protein levels, and increasing expression of BDNF and proteins associated with synaptic plasticity [29]. PACAP increases its own expression in an autocrine positive feedback loop [30].…”
Section: Discussionmentioning
confidence: 93%